2004
DOI: 10.1055/s-2004-817820
|View full text |Cite
|
Sign up to set email alerts
|

Myelofibrosis Secondary to Hyperparathyroidism

Abstract: We report on a young female who had presented with fatigue, bilateral knee pain and gait disturbance. Primary hyperparathyroidism was diagnosed together with splenomegaly and anemia. Bone marrow biopsy revealed myelofibrosis. A parathyroid adenoma was excised during surgical intervention. As early as three months after the operation, hematologic parameters improved along with bone markers without any other intervention. The control bone marrow biopsy demonstrated well marked regression in marrow fibrosis. Her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
(31 reference statements)
0
15
1
1
Order By: Relevance
“…(3032) Chronic HPT results in severe metabolic bone disease. In addition to the bone abnormalities described herein, HPT patients are anemic, have disturbed immune function,(3336) and show a marked accumulation of hematopoietic-derived mast cells in their bone marrow. 37 Mast cells play a key role in innate immunity.…”
Section: Discussionmentioning
confidence: 77%
“…(3032) Chronic HPT results in severe metabolic bone disease. In addition to the bone abnormalities described herein, HPT patients are anemic, have disturbed immune function,(3336) and show a marked accumulation of hematopoietic-derived mast cells in their bone marrow. 37 Mast cells play a key role in innate immunity.…”
Section: Discussionmentioning
confidence: 77%
“…Bone pathology shows spicules of woven bone and undermineralized bone matrix embedded in a mass of connective tissue made of abnormal, poorly differentiated stromal cells (Marie, et al 1997; Riminucci, et al 1997; Riminucci, et al 1999). This fibrosis is reminiscent of that seen in patients with severe primary or secondary hyperparathyroidism (Kumbasar, et al 2004). Likewise, mice expressing a constitutively active PTH1R mutant also display significant accumulation of fibroblastoid cells in the bone marrow (Calvi et al 2001), indicating a major role for enhanced PTH actions in the pathogenesis of fibrous dysplasia.…”
Section: Human Disorders Caused By Mutations In the Gene Encoding Gsαmentioning
confidence: 78%
“…There have been only a few reports of a primary HP accompanied by myelofibrosis. Kumbasar et al. (2004) reported a patient with parathyroid adenoma, anemia and myelofibrosis, which improved after parathyroidectomy.…”
Section: Discussionmentioning
confidence: 93%
“…Myelofibrosis, in association with anemia, has been identified in some studies (Yetgin et al, 1989;Rao, Shih & Mohini, 1993;Komatsuda et al, 1998;Duarte et al, 2002;Kumbasar et al, 2004;Lotinun, Sibonga & Turner, 2006). It has been suggested that elevated levels of PTH stimulate marrow fibroblasts, resulting in myelofibrosis (Rao, Shih & Mohini, 1993;Nomura et al, 1996).…”
Section: Discussionmentioning
confidence: 99%